PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE JIGSAW PADA MATA PELAJARAN PAI DI KELAS VII-I PUTRI SMP IT ASY-SYADZILI PAKIS MALANG - Lailatil Faiqoh; Khoirul Asfiyak; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The improvement of students' learning motivation in PAI Subjects in Class VII-I Girls of SMP IT Asy-Syadzili Pakis is discussed in this study using the Jigsaw Type Cooperative Learning Model. The goal of this study was to analyze the Jigsaw model's learning process and examine how this learning model's deployment affected student motivation. The Jigsaw technique is the subject of this classroom action research, which is being conducted with female students in class VII. Interviews, distributed questionnaires, and observations were used to determine the level of motivation. A cycle model, consisting of planning, implementation, observation, and reflection, is used in this study. The outcomes demonstrated that using the Jigsaw model helped boost students' motivation to learn. increased pre-cycle learning motivation